PowerPoint, communication, and the knowledge society - Knoblauch, Hubert (Cambridge Cambridge University Press, 2013)
"PowerPoint has become an integral part of academic and professional life across the globe. In this book, Hubert Knoblauch offers the first complete analysis of the PowerPoint presentation as a form of communication. Knoblauch charts the diffusion of PowerPoint and explores its significance as a ubiquitous and influential element of contemporary communication culture. His analysis considers the social and intellectual implications of the genre, focusing on the dynamic relationships between the aural, visual and physical dimensions of PowerPoint presentations, as well as the diverse institutional contexts in which these presentations take place. Ultimately, Knoblauch argues that the parameters of the PowerPoint genre frames the ways in which information is presented, validated and absorbed, with ambiguous consequences for the acquisition and transmission of knowledge. This original and timely book is relevant to scholars of communications, sociology and education" -- Provided by publisher.
Acknowledgments; -- Part I. Introduction: 1. 'PowerPoint' and powerpoint; 2. Communication culture; 3. Information and knowledge society; 4. Structure of the book; -- Part II. On the History of PowerPoint: 5. The archaeology of PowerPoint; 6. The double invention of PowerPoint; 7. Presentation as digital document and presentation as event; 8. PowerPoint is evil -- discourse and studies on PowerPoint; 9. Tufte and the public discourse on PowerPoint; 10. The inconclusiveness of studies on PowerPoint; 11. Presentation as event and genre; -- Part III. Communicative Action, Culture, and the Analysis of Communicative Genres: 12. Communicative actions and genres; 13. The three levels of genre analysis and communication culture; -- Part IV. The Internal Level: Slides, Speech, and Synchronization: 14. Rhetoric of visual presentation; 15. Slides, text, and speech; 16. Multimodality and the synchronization of speech slides; 17. Speech and talk; 18. Linguistic deixis, paralleling, and communicative things; 19. Lists and seriality; 20. Macrostructures; -- Part V. The Intermediate Level: Pointing, the Body Formation, and the Triadic Structure of PowerPoint Presentations: 21. Pointing, gesture, and speech; 22. Pointing, speech, and the objectification of meaning; 23. Body formation and the triadic structure of the presentation; 24. Technology, failures and footing; -- Part VI. The External Level: Settings, Meetings, and the Ubiquity of PowerPoint: 25. Objects, settings, and spaces; 26. The temporal order of presentations and the meeting; 27. The multiplication and the ubiquity of PowerPoint presentation; -- Part VII. Conclusion: the Ubiquity of PowerPoint and the Communicative Culture of Knowledge Society: 28. The invention and ubiquity of PowerPoint presentations; 29. Contextualization and mediatization; 30. Communicative things and the subjectification of knowledge; 31. PowerPoint presentation in the communicative culture of knowledge society; -- Part VIII. Appendices: Appendix 1; Appendix 2; Appendix 3; Appendix 4; References; Index.
Includes bibliographical references (pages 231-243) and index.
Keywords: Microsoft PowerPoint (Computer file).; Presentation graphics software; Communication; Information society